SCIENTIFIC AND METHODOLOGICAL BASES OF STUDYING THE PROBLEM OF USING MODERN TEACHING TECHNOLOGIES IN EDUCATION PROBLEMS OF USING MODERN TEACHING TECHNOLOGIES - Saparov Saidqul Khojamurotovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article provides analytical information on the problems of the use of new technologies in education and the scientific and methodological basis for the study of the use of modern teaching technologies in education. Also, science-based proposals and recommendations for further improvement of the educational process in Uzbekistan have been developed.